Periodized carbohydrate intake influences metabolic flexibility and indices of running economy during endurance training in recreationally active males - Kripp, Anna Maria; Feichter, Andreas; König, Daniel (Frontiers in Nutrition, 2026)
PurposeLimited research has explored the long-term impact of diet periodization on metabolism, performance, and body composition. This eight-week study examined the effects of long-term periodized carbohydrate (CHO) intake on performance, substrate utilization, and body composition in recreationally active males.MethodsTwenty-four runners (V̇O2 peak: 51 ± 8 mL·min−1·kg−1) were randomly assigned to one nutritional intervention: (1) PER: 4 weeks of ≤ 50 g CHO per day followed by 4 weeks of high CHO; (2) LCHF: 8 weeks of ≤ 50 g CHO per day; or (3) CHO: 8 weeks of high CHO. All subjects underwent the same endurance training. Performance and substrate use were measured using a graded exercise test at baseline (T-0), after 4 weeks (T-1), and after 8 weeks (T-2). Body weight and composition were measured using bioelectrical impedance analysis.ResultsWhile performance improved over time, no significant differences were found between groups. However, running economy at lactate threshold only improved in the PER group (p < 0.05). Fat oxidation increased from T-0 to T-1 in PER and LCHF group (p < 0.001), accompanied by a decrease in CHO oxidation at the lactate threshold (p < 0.001). In the LCHF group, no further changes occurred, whereas in the PER group fat oxidation decreased and CHO oxidation increased from T-1 to T-2 (p < 0.001). Both PER and LCHF group lost weight and fat mass from T-0 to T-1, with further losses in the LCHF group (p < 0.001).ConclusionA LCHF diet increased fat oxidation while reducing carbohydrate utilization during exercise. Reintroduction of carbohydrates restored substrate utilization patterns, indicating reversible changes in metabolic flexibility. However, no clear effects on performance outcomes were observed. These findings suggest that periodized carbohydrate intake primarily influences metabolic responses rather than performance, and further research using performance-based assessments is warranted. These adaptations appear to be predominantly metabolic and physiological in nature.Clinical trial registrationhttps://doi.org/10.17605/OSF.IO/VM7KB.